HUBUNGAN TEMAN SEBAYA YANG BERKUALITAS DAN PEMANFAATAN MEDIA MASSA MENINGKATKAN KECERDASAN SOSIAL ATLET MUDA - Ghozaly, Laura Florensia; Krisnatuti, Diah; Alfiasari, Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2012)
Adolescent life, including young athletes, can not be separated from their interaction with peer group and also technology of mass media. Social intelligence aspect is also important factor that influences young athletes’ achievement. The aim of this research was to investigate the influence of peer group and mass media toward social intelligences of young athletes. This study used cross-sectional study with cluster random sampling study design. Data collected by self-report that used reliable instrument. Participants in this study were 85 young athletes of eleventh grade students of sports high school in Jakarta. Result revealed that maternal age, parental status, quality of friendships with peer group, and utilization of mass media influenced social intelligence of young athletes.